2013
DOI: 10.1007/s00701-013-1875-x
|View full text |Cite
|
Sign up to set email alerts
|

Infection surveillance in transsphenoidal pituitary surgery - comparison of lipopolysaccharide-binding-protein, interleukin 6, C-reactive protein, white blood cell count, erythrocyte sedimentation rate and body temperature

Abstract: The present study establishes normative values for an infection surveillance following transsphenoidal pituitary surgery. CRP, a convenient and reasonable priced parameter, is affected by the procedure for the first postoperative week. IL-6 is more robust and allows a close monitoring on the expense of additional pricing. ESR, WBC and LBP are sustained affected by surgery, and do not offer any advantage. Since no infections were observed, we were unable to calculate the respective sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…8) Klinger et al established normative values for infection surveillance following trans-sphenoidal surgery. 12) In their study, ESR, WBC count, and lipopolysaccharide-binding-protein were affected by the surgery, and they did not offer any advantage. 12) Kuhn et al investigated 75 fusion surgery and spinal instrumentation patients and found that ESR peaked in the first week after surgery in 98% of patients, and it stayed high in the absence of infection in 78% and 53% of patients for the first and third month, respectively.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8) Klinger et al established normative values for infection surveillance following trans-sphenoidal surgery. 12) In their study, ESR, WBC count, and lipopolysaccharide-binding-protein were affected by the surgery, and they did not offer any advantage. 12) Kuhn et al investigated 75 fusion surgery and spinal instrumentation patients and found that ESR peaked in the first week after surgery in 98% of patients, and it stayed high in the absence of infection in 78% and 53% of patients for the first and third month, respectively.…”
Section: Discussionmentioning
confidence: 89%
“… 12) In their study, ESR, WBC count, and lipopolysaccharide-binding-protein were affected by the surgery, and they did not offer any advantage. 12) Kuhn et al investigated 75 fusion surgery and spinal instrumentation patients and found that ESR peaked in the first week after surgery in 98% of patients, and it stayed high in the absence of infection in 78% and 53% of patients for the first and third month, respectively. 14) An abnormal increase in WBC count during the first postoperative month was observed in 6% of these patients.…”
Section: Discussionmentioning
confidence: 89%
“…Blood biochemical tests are the most easily obtained biological information in postoperative management and can be repeated without the need for invasive lumbar puncture. 23 The baseline of CRP changes after transsphenoidal surgery. 23 CRP increased to a maximum of 2.5 mg/dL the day after surgery and had normalized 1 week later.…”
Section: Discussionmentioning
confidence: 99%
“…It is known how the inflammatory response, which develops as a response of the host to infections, occurs. Similar inflammatory response may develop after any type of tissue damage such as pancreatitis, major trauma, burns and autoimmune diseases [2][3][4] . General systemic findings of systemic inflammation (SIRS=Systemic Inflammatory Response Syndrome) such as changes in body temperature, leukocytosis, tachycardia may have infectious or noninfectious etiology.…”
Section: Despitementioning
confidence: 99%